2017
DOI: 10.1016/j.bpj.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Dependent Role of I Kur in Human Atrial Repolarization and Atrial Fibrillation Maintenance

Abstract: The atrial-specific ultrarapid delayed rectifier K þ current (I Kur ) inactivates slowly but completely at depolarized voltages. The consequences for I Kur rate-dependence have not been analyzed in detail and currently available mathematical action-potential (AP) models do not take into account experimentally observed I Kur inactivation dynamics. Here, we developed an updated formulation of I Kur inactivation that accurately reproduces time-, voltage-, and frequency-dependent inactivation. We then modified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 43 publications
(56 reference statements)
3
28
0
Order By: Relevance
“…This is a favorable drug property to avoid harmful AP prolongation (which is also limited by the reduced basal APD) if AF is terminated. Similar to Aguilar et al ( 2017 ), our results suggest that the APD- (and ERP)-prolonging effect of I Kur block is not affected by I Kur downregulation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is a favorable drug property to avoid harmful AP prolongation (which is also limited by the reduced basal APD) if AF is terminated. Similar to Aguilar et al ( 2017 ), our results suggest that the APD- (and ERP)-prolonging effect of I Kur block is not affected by I Kur downregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the consequences of I Kur inhibition, including the extent of AP and ERP prolongation, depend not only on I Kur magnitude (i.e., maximal conductance), but also on other fluxes affected by AF-induced remodeling, which affect E m and thus E m -dependent properties of I Kur (Figure 7 ). For example, our group and others have hypothesized that the extent of AP and ERP prolongation due to I Kur blockade depends on the AF-induced remodeling of other K + currents (Lagrutta et al, 2006 ; Morotti et al, 2016a ; Aguilar et al, 2017 ; Colman et al, 2017 ), and relative strengths of I CaL and I Kur (Wettwer et al, 2004 ; Grandi and Maleckar, 2016 ). Our sensitivity analysis (Figure 1C and Figures S1 – S6 ) revealed that APD 90 and ERP are more sensitive to changes in G Kur at fast vs. slow pacing rates.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sánchez et al 143 reported a systematic characterization of the importance of transmembrane ionic currents in modulating the electrophysiological properties and reentrant activity in 2D simulations of human atrial isotropic and homogeneous tissue. Aguilar et al 144 used 2D simulations to study the rate-dependent role of I Kur and the effect of blocking it on the atrial AP. Keller et al 145 used a 3D isotropic planar patch of myocardium to stablish a model for acute ablation lesions in order to study the changes in the EGMs during radio-frequency ablation procedures.…”
Section: D Atrial Modelsmentioning
confidence: 99%